How do Spot prices affect aggregate electricity demand? - Torstein Bye; Petter Vegard Hansen (Statistics Norway, Research Department, 2008)
All participants in power exchanges are interested in market responses when electricity prices change because this influences the profitability of actions. Contrary to most econometric work in this field, which uses annual time series or panel data, we exploit high-frequency data from a power exchange to estimate the spot price elasticities of the total market and of different market segments. The use of such data requires a simultaneous market model including both behavioral and control variables to capture short-term shifts in both demand and supply. Compared with Wolfram (1999) our short-term responses to spot market prices are not straightforward because the picture is confused by differences in production flexibilities in a complex and heterogeneous supply side, demand technologies and a combination of different end-user contracts. We show that short- and long-run price effects on demand differ significantly among hours, weekdays, seasons, and countries.
Keywords: Q41; D01; D51; 330; Electricity demand; Simultaneous markets; High Frequent data; Electricity Exhange